The effect of a superhydrophobic coating on moisture absorption and tensile strength of 3D-printed carbon-fibre/polyamide. (June 2021) - Kreider, P.B.; Cardew-Hall, A.; Sommacal, S.; Chadwick, A.; Hümbert, S.; Nowotny, S.; Nisbet, D.; Tricoli, A.; Compston, P.
Abstract: This work investigates the effectiveness of fluorinated silica-based superhydrophobic coatings to protect 3D-printed carbon-fibre/polyamide composites against moisture-induced degradation. Increasing exposure time in wet and humid environments led to a reduction of tensile strength and an increase in experienced strain. However, the coated PA demonstrated 6.7–12.4% higher tensile yield strength than the uncoated PA. High-resolution X-ray micro computed tomography (μCT) was used to image the microstructure and revealed that the superhydrophobic coating effectively prevented liquid water penetration into 3D-printed polyamide and delayed water vapour-driven mechanical degradation. The presence of the superhydrophobic coating eliminated the liquid water presence in the surface features of the PA matrix and reduced the moisture-induced swelling of the polyamide matrix by about 53% after 168 h under water. Further optimisation of these coatings may provide a solution to enhance the performance of PA composites in humid and wet environments.